BUDAYA 3S: GERAKAN INTELEKTUAL KOLEKTIF KAMPUNG MUHAJIRUN DALAM MEMBANGUN HARMONI DI NATAR LAMPUNG SELATAN - Aisyah Khumairo (Postgraduate State Islamic Institute (IAIN) Metro, 2019)
This research aims to find out the culture of the 3S collective intellectual movement in the village of muhajirun natar lampung selatan in building harmony. In this study using a phenomenological approach, which is a study that describes the phenomena of human life in everyday social contexts, where phenomena occur from the perspective of those who experience them or rely on the perspective of actors and try to understand observations from subjective perspectives. The results of this study indicate the results of the strategy of the Muhajirun village community in introducing a culture of smiling greetings to the general public such as socialization through socialization in majlis ta'lim, socialization in educational institutions, in open society, by reminding one another and setting an example.